Occupational Health Hazards Among Workers of Garment Factories in Dhaka City, Bangladesh - Khan, Nirmeen Rifat; Dipti, Tanjeem Rabika; Ferdousi, Syeda Khaleda; Hossain, Mohammad Zaid; Ferdousi, Sultana; Sony, Sadia Akther; Zafrin, Nahida; Paul, Nandita; Islam, Mohammad Shohidul (Journal of Dhaka Medical College, 2016)
A cross-sectional study was conducted from January to June of 2013 to find out the occupational health hazards among the workers of different garment factories in Dhaka, Bangladesh. Total sample was 145 and purposive sampling technique was followed for data collection, which was done by face to face interview. The data was collected on a structured questionnaire. Data was analyzed by SPSS version 17.0. Majority (40%) were found in the age group of 16-20 years where mean age was 23.30 ±6.92 years. Among them female (89%) outnumbered the male (11%). Of them 96% were Muslim. Majority (48.3%) were educated up to primary school and most of them (55.9%) were married. 91.7% had monthly salary of 1001-5000 taka. 52.4% respondents were machine operator, but maximum (75%) were unskilled and 72% had length of job between 2-7 years. 91% respondents normally worked for 8-9 hours. 85.5% did 2-3 hours overtime. In the last one year 64.8% had no accident but minor cut, burn or injury was faced by 28.3%. Most of the (44%) respondents did not complain about physical environmental pollution but 33.8% complained of noise pollution. Majority (84.8%) were satisfied with the constant presence of doctor or nurse in their factory. Maximum (51%) respondents suffered from headache or shoulder pain. Insomnia was common in 20% respondents. Majority (56.6%) did not mention any permanent illness. In this study the prevalence of occupational health hazards was 88.28%. A significant relationship was found between noise pollution and headache (P<0.014) and also between length of job (in years) & backache (P<0.091). More emphasis should be given to the workers to improve their health condition and working environment, so that they can increase their efficiency which can ultimately increase the production and add GDP to the country. J Dhaka Medical College, Vol. 24, No.1, April, 2015, Page 36-43